The Natural-Scientific Heritage of The Khwarezm Ma’mun Academy and Its Socio- Philosophical Views - Kamilovna, Masharipova Gularam – (International Journal of Psychosocial Rehabilitation, 2020)
The rich natural-scientific heritage and socio-philosophical views of the scholars of Khwarezm Ma’mun academy are scientifically analyzed in the article. The rich scientific researches of the Muhammad ibn Musa al-Khwarezmi, Abu Raykhan Beruni, Abu Nasr ibn Iraq and Abu Ali ibn Sina over the precise disciplines and their socio-political views are studied on the basis of the miscellaneous sources.